Can coffee silverskin be a useful tool to fight metabolic syndrome? - Andrade, Nelson; Peixoto, Juliana A. Barreto; Oliveira, M. Beatriz P. P.; Martel, Fátima; Alves, Rita C. (Frontiers in Nutrition, 2022)
Coffee is one of the most consumed products in the world, and its by-products are mainly discarded as waste. In order to solve this problem and in the context of a sustainable industrial attitude, coffee by-products have been studied concerning their chemical and nutritional features for a potential application in foodstuffs or dietary supplements. Under this perspective, coffee silverskin, the main by-product of coffee roasting, stands out as a noteworthy source of nutrients and remarkable bioactive compounds, such as chlorogenic acids, caffeine, and melanoidins, among others. Such compounds have been demonstrating beneficial health properties in the context of metabolic disorders. This mini-review compiles and discusses the potential health benefits of coffee silverskin and its main bioactive components on metabolic syndrome, highlighting the main biochemical mechanisms involved, namely their effects upon intestinal sugar uptake, glucose and lipids metabolism, oxidative stress, and gut microbiota. Even though additional research on this coffee by-product is needed, silverskin can be highlighted as an interesting source of compounds that could be used in the prevention or co-treatment of metabolic syndrome. Simultaneously, the valorization of this by-product also responds to the sustainability and circular economy needs of the coffee chain.